Pengaruh Sejarah Gereja Dalam Perjalanan Sejarah Keuskupan Agung Pontianak Dan Perkembangannya Dewasa Ini - Antonius Denny Firmanto; Nanik Wijiyati Aluwesia; Aman Aman (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2022)
The focus of this research is to recognize and understand the history of the Pontianak Archdiocese Church in the course of Church history. Many people do not know the history of the Pontianak Archdiocese. However, the splendor of the Pontianak Archdiocese Church is well known, even abroad, especially in the Vatican Rome. In this study, the researcher used a qualitative methodology with a literature study approach regarding the Influence of Church History in the History of the Pontianak Archdiocese and current developments. Researchers used book sources, journal sources, and internet sources. History is an event and events that really happened in the past. The church is an association of people who follow Jesus Christ. Church history is a journey of the past of the Church that has occurred after the coming of Jesus Christ. Church history does not just appear but is a legacy of Church Fathers who were willing to be martyred in order to fight for and at the same time defend the truth of the faith. The church's mission is to bring people to God's salvation. The Pontifical Archdiocese Church has a long history, and has faced challenges and obstacles, both internally and externally. What started as the Apostolic Vicariate of Dutch Borneo, changed to the Archdiocese of Pontianak. Studying the history of the Pontianak Archdiocese Church is something that must be continued because that is where researchers get a very meaningful understanding. So this article aims to understand how the history of the Church and the history of the Pontifical Archdiocese has grown and developed today. The results of this study indicate that the Historical Journey of the Pontianak Archdiocese follows the journey of early Church history that was championed by the Church Fathers. Thus it can be concluded that the emergence of the history of the Archdiocese of Pontianak came from foreign missionaries.